Analisis Analisis Pisikologi Sastra Tokoh Utama Dalam Cerpen Bahasa Bali Stri Ngarania Apuy Padania Karya I Made Suarsa - Nurrohmah, Siti; Sulibra, I Ketut Ngurah; Puspawati, Luh Putu (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
This literary psychology analysis examines the main character in the Balinese short story